13th Malaysian general election : prospects and challenges for PAS - Farish A. Noor (2013)
The controversy over the use "Allah" by non-Muslims in Malaysia is one of the many tough issues that PAS has to deal with as a member of the Pakatan Rakyat opposition coalition which seeks to capture power in the coming general election. Can PAS walk the tightrope between political idealism and pragmatism should the opposition run the country.